Typicality analysis on statistical shape model-based average head and its head-related transfer functions - Wang, Yewei; Yu, Guangzheng (The Journal of the Acoustical Society of America, 2025)
In acoustics, an artificial head generally comprises two pinnae and occasionally a torso, which are useful for recording binaural signals and acquiring head-related transfer functions (HRTFs). Currently, most artificial heads are designed based on the anthropometric parameters of specific populations. However, anthropometric parameters do not accurately express head surface shapes, and thus, typical HRTFs are difficult to generate. Thus, this study presents a statistical shape model-based average head of 100 Chinese adults and comprehensively presents its repeatable design process. Furthermore, to validate the representativeness of the statistical shape model-based average head in terms of the head surface shape features and acoustical characteristics, its anthropometric parameters are compared with those of the 100 subjects. Moreover, the representativeness of statistical shape model-based average head's HRTFs is verified through the typical HRTFs clustered from the entire HRTF database. Owing to the clear and concise design process, the proposed method can be easily applied and promoted to a new population.